Comunidades historiográficas y renovación disciplinaria en Uruguay - Zubillaga, Carlos (Revista Complutense de Historia de América, 2003)
In Uruguay, although the beginnings of XXth century some innovations were formulated on the theoretical basis and the utility of the historical knowledge, it was just in the immediate second world-wide postwar period that they found ways for development in the activity of Museo Histórico Nacional (urging a tendency of active nationalism) and Facultad de Humanidades y Ciencias of the state Universidad de la República (in wich a tendency of universal insertion of the national past was developed). The tension between both conceptions (that it did not exclude the sum of its efforts) influenced the renovation of predominant historiographical paradigm in academic communities until present.